Effect of intraoperative treatment options on hip joint stability following total hip arthroplasty. Issue 3 (29th April 2021) - Myers, Casey A.; Huff, Daniel N.; Mason, J. Bohannon; Rullkoetter, Paul J.
Abstract: Dislocation remains the leading indication for revision of total hip arthroplasty (THA). The objective of this study was to use a computational model to compare the overall resistance to both anterior and posterior dislocation for the available THA constructs commonly considered by surgeons attempting to produce a stable joint. Patient‐specific musculoskeletal models of THA patients performing activities consistent with anterior and posterior dislocation were developed to calculate joint contact forces and joint positions used for simulations of dislocation in a finite element model of the implanted hip that included an experimentally calibrated hip capsule representation. Dislocations were then performed with consideration of offset using +5 and +9 offset, iteratively with three lipped liner variations in jump distance (10°, 15°, and 20° lips), a size 40 head, and a dual‐mobility construct. Dislocation resistance was quantified as the moment required to dislocate the hip and the integral of the moment‐flexion angle (dislocation energy). Increasing head diameter increased resistive moment on average for anterior and posterior dislocation by 22% relative to a neutral configuration. A lipped liner resulted in increases in the resistive moment to posterior dislocation of 9%, 19%, and 47% for 10°, 15°, and 20° lips, a sensitivity of approximately 2.8 Nm/mm of additional jump distance. A dual‐mobility acetabular design resulted in an average 38% increase in resistive moment and 92% increase in dislocation energy for anterior and posterior dislocation. A quantitative understanding of tradeoffs in the dislocation risk inherent to THA construct options is valuable in supporting surgical decision making.